Identity – towards a conceptualization - Barros, Teresa (2009)
The development of economical relations increases the interaction between organizations and stakeholders. It is no more acceptable to manage an organization under a transactional perspective where suppliers had a fundamental role. Nowadays organizations are being managed under a relational perspective where relations and relationship management in general have consequences in identity management (Hakansson e Snehota, 1989, 1995). A correct perception and management of identity is necessary to achieve distinctiveness in the competitive environment. This way, identity is influenced by relations with stakeholders in general and particularly with competitors. The ICIG concept states that identity is related with the values of the organization and it helps creating distinctiveness in the competitive environment (Van Riel, Balmer, 1997); Baker and Balmer (1997) state that identity is what the organization is; Suvatjis and de Chernatony (2005) refer that expressing identity is a dynamic process that evolves the use of a management model to face context changes; Kapferer (1991) states that brand identity is the project, the self conception of the brand. After reviewing and confronting literature under the plethora of identities’ concepts and perspectives (He, Balmer, 2007) one can’t find an integrative answer with all the elements that contribute to identity of organizations. The authors are strongly interested to contribute to the elimination of this limitation and to answer to strategic management needs. In a marketing context one can find: - the corporate identity approach that is focused in the distinctive attributes of an organization (Abratt, Balmer, Marwick e Fill, Stuart, Balmer and Gray, Alessandri, Suvatjis and de Chernatony) - the brand identity approach (related with the application of corporate identity studies to brands) - Kapferer, Semprini, Aaker, de Chernatony). Kapferer (1991), one of the most prolific authors in this field was the first author to integrate identity in a brand concept. In his view, identity is an emission concept. This idea is shared also by Aaker (1996). Yet, identity has to be managed in a competitive environment which is constantly changing. After reviewing and confronting literature, authors select concepts that are generally accepted by the investigators in order to design a model to analyze and manage identity: - corporate identity models: personality, image/reputation, culture, philosophy, mission, strategy, structure, communication - some of these concepts derive from identity models and others from identity management models; - brand identity models – Kapferer (1991, 2008) identity prism, witch is basis of literature in this field: culture, physical facet, personality, relationship (between brand and consumer), reflected consumer, consumers` self-concept. After discussion authors decide to include other concept in line with other authors` view: country of origin (Aaker, 1996). A discussion eliminates the twin concepts and the final selection is as follows: personality, image/reputation, culture (including philosophy and mission), strategy, structure, communication, culture, physical facet, relationship (between brand and consumer), reflected consumer, consumers` self-concept and according to authors` reflections “relationships” deriving from competitors` actions in competitive environment. Competitors’ actions and decisions have a stronger influence in the organizations` positioning than any other stakeholder as stated before. This is a work in progress towards a new model in identity analysis and management so an exploratory study will follow inquiring experts on identity in order to evaluate these concepts and correct the theoretical perspectives.